2003
DOI: 10.1074/jbc.m301470200
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Chimeric Epidermal Growth Factor-like Module with High Binding Affinity for Integrins

Abstract: Integrins are cell surface receptors involved in numerous pathological processes such as metastasis invasion and abnormal angiogenesis. To target these receptors, the epidermal growth factor (EGF)-like domain of human complement protease C1r was used as a natural scaffold to design chimeric modules containing the RGD motif. Here we report a high yield bacterial expression system and its application to the production of two such modules, EGF-RGD and V2, the latter variant mimicking the RGD-containing domain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The improvement of the cell adhesion activities of the EGF module through the use of the RGD sequence was reported by Vella et al [36,41]. Reddy et al [3] reported the enhancement of the mitogenic potency of EGF through the use of specific mutations.…”
Section: Egf Activity On the Plate Surfacementioning
confidence: 87%
“…The improvement of the cell adhesion activities of the EGF module through the use of the RGD sequence was reported by Vella et al [36,41]. Reddy et al [3] reported the enhancement of the mitogenic potency of EGF through the use of specific mutations.…”
Section: Egf Activity On the Plate Surfacementioning
confidence: 87%
“…SPR has already been used for the investigation of different integrin–ligand interactions, like the binding between integrins α 1 β 1 and α 2 β 1 and collagen type I, or the interaction between a recombinant chimeric epidermal growth factor‐like module and integrins α 5 β 1 , α v β 3 and α IIb β 3 18. 19 Here we describe for the first time the application of SPR to the analysis of the interaction between fibronectin and integrin α 5 β 1 . SPR usually relies on the application of purified interaction partners.…”
Section: Ic50 Values Of α5β1 Ligands As Determined From the Cell‐adhementioning
confidence: 99%